A legal study on minimum wage in the private sectors in Malaysia / Jacqueline Charlie ... [et al.] - Charlie, Jacqueline; Roslan, Izzati; Freddy, Sandy Yvette; Kamarzaman, Nur Hafizah Izani; Wan Shamsuddin, Wan Hazwani; Abd Aziz, Zatil Atteya (2010)
This research contributes to the necessity of having national minimum wage legislation in this country especially for the private sectors. It analyses the advantages and disadvantages of having the national minimum wage legislation in Malaysia. For the purpose of comparative study, this research scrutinised the law adopted in three countries namely Australia, United States and India to evaluate which is the best model of law to be follow and being incorporated in the national minimum wage legislation in Malaysia. In carrying out this research, the research methods used were including library based research, internet research and semi structured interview. The fight for the introduction of a national minimum wage was spearheaded by the Malaysian Trade Union Congress (MTUC), and this effort was stepped up after the Government announced a hefty increase in the salary of government employees. The demand seems to be well-founded as the minimum wage will see the workers in the private sectors, which are not benefiting from the government salary increase to be protected. Therefore this paper suggested that a specific legislation on minimum wage is necessary especially for the private sector.